(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The study was designed to explore the status of fishers access to the common property waterbodies (CPW) and associated problems of using CPW. Three upazillas (administrative units) of the Northern region of Bangladesh were selected for the empirical study. Data were collected from fishers, non-fishers and other stakeholders through structured interview schedules, physical observation, and participatory rural appraisal (PRA). The access of poor fishers group to the CPW was very limited in the study area. The government policy of revenue collection through leasing system badly affected the fishers group as they do not have required level of capital, unity, leadership and education. A revenue oriented fisheries management system with short lease periods was found to encourage over-fishing and destructive fishing by lessees, where the lessees were noted to sweep away all the fish stock as soon as their contract ended without considering the sustainable use of resource and biodiversity. Consequently, the productivity of the CPW is declining gradually. To ensure the effective access of fishers group to CPW and their sustainable use, an advised long-term community based management (CBM) plan needs to be developed with the effective participation of the fishers groups and other stakeholders. Res. Agric., Livest. Fish.2(1): 125-133, April 2015